2018
DOI: 10.1002/mnfr.201700975
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Metabolite Concentrations after a Low‐Glycemic Index Diet Intervention

Abstract: These results suggest that an LGI diet modulates certain circulating amino acids and lipid levels. These findings may explain the health benefits attributed to LGI diets in metabolic diseases such as type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
(62 reference statements)
1
20
0
Order By: Relevance
“…The third block comprises three studies that used metabolomics to predict weight loss (Geidenstam et al 2017a , b ; Stroeve et al 2016 ) and 11 randomized clinical trials (RCTs) aimed to assess the effects of weight loss interventions (both hypocaloric diet programs and exercise interventions) on the metabolomic profiles of overweight or obese human subjects (Table 2 ) (Almanza-Aguilera et al 2018 ; Duft et al 2017 ; Kang et al 2018 ; Leal-Witt et al 2018 ; Meucci et al 2017 ; Mills et al 2019 ; Munukka et al 2018 ; Palau-Rodriguez et al 2019 ; Perez-Cornago et al 2014 ; Zheng et al 2016a , b ). Additionally, the fourth block includes 11 articles that studied the effects of specific dietary patterns or dietary compounds on obesity-related metabolic alterations in humans, such as inflammation or oxidative stress (Table 3 ) (Baldrick et al 2018 ; Gu et al 2013 ; Hernández-Alonso et al 2019 ; Hibberd et al 2019 ; Kim et al 2013 ; Kim et al 2017 ; Mayengbam et al 2019 ; Nieman et al 2012a , b ; Romo-Hualde et al 2018 ; Xu et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The third block comprises three studies that used metabolomics to predict weight loss (Geidenstam et al 2017a , b ; Stroeve et al 2016 ) and 11 randomized clinical trials (RCTs) aimed to assess the effects of weight loss interventions (both hypocaloric diet programs and exercise interventions) on the metabolomic profiles of overweight or obese human subjects (Table 2 ) (Almanza-Aguilera et al 2018 ; Duft et al 2017 ; Kang et al 2018 ; Leal-Witt et al 2018 ; Meucci et al 2017 ; Mills et al 2019 ; Munukka et al 2018 ; Palau-Rodriguez et al 2019 ; Perez-Cornago et al 2014 ; Zheng et al 2016a , b ). Additionally, the fourth block includes 11 articles that studied the effects of specific dietary patterns or dietary compounds on obesity-related metabolic alterations in humans, such as inflammation or oxidative stress (Table 3 ) (Baldrick et al 2018 ; Gu et al 2013 ; Hernández-Alonso et al 2019 ; Hibberd et al 2019 ; Kim et al 2013 ; Kim et al 2017 ; Mayengbam et al 2019 ; Nieman et al 2012a , b ; Romo-Hualde et al 2018 ; Xu et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…At 120 min, nine metabolites (i.e., orotate, leucine/isoleucine, mesoxalate, asparagine, citrulline, methionine, allantoin, ornithine, and tyrosine) were significantly altered in the low-fat milk versus the rice beverage group. The evaluation of a low-glycemic index diet in overweight/obese adults for 6 months (Table 3 ) (Hernández-Alonso et al 2019 ) revealed several changes. The plasma serine levels were significantly increased following the low glycemic index diet compared to both the high glycemic index and low-fat diets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the possible effects intrinsic to pea and barley compounds making them functional foods, there is still the possibility that the lipid-lowering effect of pea and barley is associated to the diet's glycemic index. A recent metabolomic study with obese humans found differential regulation of certain amino acids and phospholipids depending on the diet's glycemic index [46], which could contribute to explain the lipid-lowering effects attributed to low-glycemic index diet on diabetic or hyperlipidemic humans reported previously [47,48]. It was not measured in our study, but we have already shown that a pea and barley-based diet generate lower glycemic variables in diabetic dogs when compared to a maizebased diet [29].…”
Section: Discussionmentioning
confidence: 50%
“…Bucketing (6e-04 ppm as bucket width), referencing to TSP at 0 ppm and probabilistic quotient normalization 17 were performed through rDolphin. 18 In the serum dataset, sample collection details are available in Hernández-Alonso, P. et al 19 For each sample, 300 μ l aliquots were mixed with 300 μ l of sodium phosphate buffer. Carr…”
Section: Datasetsmentioning
confidence: 99%